A NEW APPROACH TO STRATEGIC PLANNING IN ENTREPRENEURIAL PROCESS: EFFECTUATION - Baykal, Bilge (PEOPLE: International Journal of Social Sciences, 2015)
The development and implementation of strategy within entrepreneurial organizations require skills and the ability to perceive environmental shifts and adapt accordingly to ensure organizational growth and preserve the resources of the firm. The entrepreneur must have an intimate knowledge of the business plus intuition and resourcefulness to successfully transform the strategy from its initial intent to one that accommodates the external forces and responds to its environment. This study presents an exploratory approach to describe and compare the formal and informal strategic planning processes of entrepreneurial organizations particularly focusing on new ventures. This study provides a conceptual framework for strategic planning of new venture entrepreneurial process by an integrated perspective of formal and informal approach, which is named as "Effectuative Entrepreneurial Process Framework". The framework presented in the study includes causal sequence components of the formal entrepreneurial process while considering the intuitive and creative part of the entrepreneurial process having components of cognitive adaptability of entrepreneurs and inter-firm and intra-firm strategic flexibility.